Vzorník 2012 - Čagánek, Michal, 1978-; Vlček, Tomáš, 1970-; Hložek, Ondřej, 1986-; Keroušová, Michaela, 1987-; Kestřánková, Agáta, 1996-; Koláček, Martin, 1981-; Straka, Josef, 1972-; Sviták, Jan, 1983-; Šindelka, Marek, 1984-; Šťastný, Milan, 1973- (E-knihovna. Vzorníky, 2012)
Sborník Městské knihovny v Praze obsahuje kratší texty devíti současných českých autorů poezie i prózy.